Does Economic Overheating Provide Positive Feedback on Population Health? Evidence From BRICS and ASEAN Countries - Su, Chi-Wei; Huang, Shi-Wen; Tao, Ran; Haris, Muhammad (Frontiers in Public Health, 2021)
This paper explores the relationship of real GDP per capita with cancer incidence applying panel threshold regression model in BRICS and ASEAN countries. The empirical results highlight that the business cycle has an inverted-U correlation with population health indicators and a non-linear single threshold effect. In BRICS countries, the health-promoting effect of economic growth is significantly weaker when exceeding the threshold. Similarly, economic growth in ASEAN countries, even worsens population health, after the turning point. These asymmetric effects are strongly related to the response of regional economic globalization health policies. Changes in economic expansion and overheating may have serious adverse effects on health care systems in emerging economies. Governments should adopt more aggressive health care policies during economic overheating, to avoid wasting health care resources.